Mechanism design : visual and programmable approaches - Russell, Kevin (Mechanical engineer); Shen, Qiong (Mechanical engineer); Sodhi, R. S. (Raj S.) (Boca Raton : CRC Press, 2014)
"This book guides readers in learning how to design the most common 2D and 3D mechanical systems, able to perform in a pre-determined manner. Using the commercial mathematical software package MATLAB and its mechanical system modeling and simulation module SimMechanics, this textbook enables the reader to readily apply the design approaches presented to design mechanical systems and visualize their results. With this knowledge of theory and application, the reader will be well-equipped to invent novel mechanical system designs for a wide range of applications. "--
"Preface Kinematic synthesis of mechanisms involves performing the design to create a new mechanism, which would fulfill some given design functions. Current textbooks on mechanism design deal mostly with analyzing existing mechanisms and devote only a chapter or two to synthesis, which is not enough to provide a comprehensive introduction. Most textbooks present mainly qualitative methods for kinematic synthesis, which are based on drafting techniques. Although qualitative methods are easy to implement, they are typically limited to two-dimensional, small-scale problems. In recent times, personal computers have facilitated the design of complex systems. Computation-based or quantitative methods are far more robust in terms of the type and scale of problems that one can consider. In addition, the computing technologies available today, both hardware and software, make quantitative methods very practical. This book, which is dedicated entirely to kinematic synthesis, is based on our experience in teaching mechanism design courses as well as on our practical experience in the industry. The purpose of this textbook is to give the reader an introduction to kinematic synthesis that is both broad and practical. In terms of providing a broad introduction, this textbook presents applications of planar and spatial motion, path, and function generation methodologies (both classical and modern). Additional topics include number synthesis, the synthesis of finite and multiply separated positions, and the synthesis of adjustable mechanisms (a more modern focus on kinematic synthesis). In terms of providing a practical introduction, this textbook considers some of the most basic planar and spatial single- and multiloop linkage systems"--
Includes bibliographical references and index.
Keywords: Mechanical movements; Machinery; TECHNOLOGY & ENGINEERING / Mechanical; TECHNOLOGY & ENGINEERING / Industrial Design / General